If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + n = -4 Solving 6 + n = -4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + n = -4 + -6 Combine like terms: 6 + -6 = 0 0 + n = -4 + -6 n = -4 + -6 Combine like terms: -4 + -6 = -10 n = -10 Simplifying n = -10
| 125x+150=-150-125x | | 20=z+7 | | 3x+9-2x+5=6x-4x+7 | | 20=-16t^2+32t+100 | | (c/3)+7=5+1/2 | | (2/3)(12-x)=4 | | 67537653764=8764875x | | smile=fun | | wel=ok | | oh=56 | | 56+5= | | 67+8x=5 | | 3+8x=4x-5 | | 7x+8x=5 | | 2*2x=5 | | y=-1.2x+2/3 | | 5x/x-3=8+15/x-3 | | 6x-78/4 | | (5-3i)/(2+6i) | | x-7/3=5 | | 11x-8x=42 | | 3/5y-10=11 | | 11x+20=29 | | 500-3x=680-6x | | 500+3x=680-6x | | 5y-(y-2)=5 | | 6x+11=26 | | 4x+12=-4 | | 4x+5y=100 | | (3b+7)+(8b+3)= | | 3=3x-15 | | 2x+50=12x-10 |